Line shape of the Raman 2D peak of graphene in van der Waals heterostructures. Issue 12 (9th August 2016) - Neumann, Christoph; Banszerus, Luca; Schmitz, Michael; Reichardt, Sven; Sonntag, Jens; Taniguchi, Takashi; Watanabe, Kenji; Beschoten, Bernd; Stampfer, Christoph
Abstract: The Raman 2D line of graphene is widely used for device characterization and during device fabrication as it contains valuable information on, e.g., the direction and magnitude of mechanical strain and doping. Here, we present systematic asymmetries in the 2D line shape of exfoliated graphene and graphene grown by chemical vapor deposition. Both graphene crystals are fully encapsulated in van der Waals heterostructures, where hexagonal boron nitride and tungsten diselenide are used as substrate materials. In both material stacks, we find very low doping values and extremely homogeneous strain distributions in the graphene crystal, which is a hall mark of the outstanding electronic quality of these samples. By fitting double Lorentzian functions to the spectra to account for the contributions of inner and outer processes to the 2D peak, we find that the splitting of the sub‐peaks, 6.6 ± 0.5 cm −1 (hBN‐Gr‐WSe2 ) and 8.9 ± 1.0 cm −1 (hBN‐Gr‐hBN), is significantly lower than the values reported in previous studies on suspended graphene.